Nonconformist writing in Nazi Germany : the literature of inner emigration - Klapper, John, 1958- (Studies in German literature, linguistics, and culture., 2015)
Studies of literary responses to National Socialism have largely focused on exiled writers; opposition within Germany and Austria is less well understood. Yet in both countries there were writers who continued to publish imaginative literature that did not conform to Nazi precepts: the authors of the so-called Inner Emigration. They withdrew from the regime and sought to express their noncomformity through camouflaged texts designed to offer sensitized readers encouragement, reassurance, and consolation. This book provides an innovative, critical, historically informed, yet accessible reassessment of these writers --